(untitled) (Metallurgy and Foundry Engineering, 2013)
Many traces of copper metallurgy, such as slag and other copper melts, can be found in the area of Lower Silesia. The research programme, which assesses the exact location and detailed inventory of the sites connected with mining and copper smelting in the area of three historical regions of its exploitation, as well as testing of the collected material is implemented by the Copper Museum in Legnica, in collaboration with the Faculty of Foundry, at the University of Science and Technology. The tested material mainly consists of copper slag with different content of copper melts, being a semi product. The copper metallurgy remains, discovered during the research, undergo specialistic analyses, which will help better characterise the findings as well as contribute to documenting metallurgical processes in the historical bloomeries in Lower Silesia, and moreover to prepare further research in this field. The material coming from the area of Miedzianka, being the oldest and the longest working exploitation centre of copper ores and pollymetalic ores, is of special significance for the research. Mining activity in the area of Miedzianka took place as early as the beginning of the 14th century, the first record from 1311 (Cuprifodina in montubus) is the oldest information concerning copper mining in Poland.